A new instrument for rectal suction biopsy in the diagnosis of Hirschsprung′s disease: Triple rectal suction biopsy - Barlas Meral (Wolters Kluwer Medknow Publications, 2006)
A new instrument for suction rectal biopsy in infants suspected of having Hirschsprung′s disease is described that can be completely dismantled, physically cleaned, lubricated, and heat sterilised. Triple rectal suction biopsy instrument with the patent application, which involves (0.5 cm diameter) suction of mucosa and sub-mucosa and provides taking three different biopsies within a 2 cm distant from each other with a single shot, instead of only one or taking a full layer biopsy under general anesthesia for the diagnosis of Hirschsprung disease. As a preliminary study, in the 36 and 12 biopsy materials taken from the rabbits and children, respectively, it was found that mucosa and sub-mucosa were sufficient and in all of the cross sections, parasympathetic nerve fibers, and ganglion cells were existed. A successful biopsy was usually achieved and no complications occurred.